Formulation of silver Nanoparticle from a methanolic extract of Onosma bracteatum and evaluation of their antibacterial properties - khatri, Sweety Jaggi; Gupta, Bhaskar Kumar (Journal of Neonatal Surgery, 2025)
This study focuses on the green synthesis of silver nanoparticles (AgNPs) using the methanolic extract of Onosma bracteatum, a medicinal plant known for its antimicrobial properties. The synthesized AgNPs were characterized using UV-Vis spectroscopy, FTIR, SEM, and DLS techniques. The antimicrobial activity was evaluated against selected bacterial and fungal strains using the agar well diffusion method. Results indicated significant antimicrobial activity of the formulated AgNPs, suggesting their potential in pharmaceutical and biomedical applications. Antibacterial evaluation demonstrated that both the methanolic extract and the biosynthesized AgNPs exhibited significant activity against various bacterial strains, including Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Staphylococcus capitis. These findings suggest that the plant-derived AgNPs could serve as effective natural alternatives to conventional antibiotics. Overall, this eco-friendly synthesis approach represents a promising alternative to traditional physical and chemical nanoparticle production methods and holds potential for application in antimicrobial therapies and other biological systems